Hoarding and aggression: Using the voodoo doll task to tease apart associations with direct and displaced aggression. - Chen, Wenting; Fuller, Phaedra; Grisham, Jessica R.; Denson, Thomas F.; Timpano, Kiara R. (British Journal of Clinical Psychology, 2025)
Objectives: Hoarding disorder is a debilitating and severe psychiatric condition. Research has implicated interpersonal factors as contributing to the development and maintenance of the disorder. Emerging evidence has suggested that aggression and anger‐related concepts may contribute to these interpersonal difficulties, but aggression has only been measured thus far through self‐report, which is limited by responding biases. Methods: In the present study, we examined the associations between self‐reported hoarding symptoms and two forms of aggression using both questionnaire measures and a novel behavioural task of aggression. Participants included 466 participants from the community recruited through an online crowdsourcing platform, who completed an anger‐induction task followed by a voodoo doll task as a measure of direct and displaced aggression. Results: Results revealed that hoarding symptoms were associated with greater aggression in both self‐report and in the behavioural task. Self‐report results also indicated that the relationship with displaced aggression may be modestly stronger than that of direct aggression, accounting for covariation. Conclusions: These findings suggest that aggression may be relevant in understanding interpersonal difficulties in hoarding and may have clinical and theoretical relevance for the disorder.